The Use of Person Deixis in Balinese: A Social-Cognitive Perspective on Honorifics in the Balinese Folktale Ni Bawang teken Ni Kesuna - A.A.I. Mas Trisnamayuni; I Made Astu Mahayana (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This research explores the use of person deixis in the Balinese language, with a particular focus on the honorific system as a form of social interaction. Person deixis not only reflects the relationship between the speaker and the interlocutor but also serves as a key mechanism for expressing social status, age, and emotional closeness. This research addresses the question: Does the choice of deictic forms involve specific cognitive processes, such as the assessment of social status, politeness, and situational context? Beside that, this research also discuss what factors most influence the choice of personal pronouns used in dialogue? Employing a descriptive-qualitative approach and analyzing data from Balinese narrative texts, this article examines how the selection of deictic expressions engages complex cognitive mechanisms. The findings reveal that the use of honorifics is not merely a linguistic practice but also influences speakers’ patterns of thought in interpreting and evaluating social relationships. These results support the notion that language and thought are closely interconnected, and that the structure of the Balinese language cultivates a high degree of social sensitivity in its speakers from an early age.